UNIFORM HOSPITAL ACCOUNTING. - Rorem, C. Rufus (The Accounting Review, 1936)
Abstract The article highlights that the general advantages of uniform accounting among hospitals are the same as for business enterprises, namely, comparison of operating efficiency between hospitals and periods of time, and establishment of effective relations with the public served by the institutions. Hospitals are a combination of commercial enterprise and social agency. As a commercial enterprise a hospital may provide services to customers, that is, patients, at prices presumably based upon the costs of the services rendered. As a social agency a hospital may serve a client or customer, regardless of his ability to pay, the costs being met by some other individual or group. This dual aspect of hospital service pervades every problem of administrative practice or public relations. Governmental hospitals are, for the most part, conducted strictly as social agencies with the direct beneficiaries paying none of the costs. Privately owned hospitals, on the other hand, are conducted strictly as commercial enterprises, with the patients paying the full costs including the fixed charges, and with charity provided only by compulsion through the uncollectibility of accounts receivable. The incorporated non-profit hospitals combine both the commercial and social aspects.